2020
DOI: 10.7554/elife.60264
|View full text |Cite
|
Sign up to set email alerts
|

Protein phase separation and its role in tumorigenesis

Abstract: Cancer is a disease characterized by uncontrolled cell proliferation, but the precise pathological mechanisms underlying tumorigenesis often remain to be elucidated. In recent years, condensates formed by phase separation have emerged as a new principle governing the organization and functional regulation of cells. Increasing evidence links cancer-related mutations to aberrantly altered condensate assembly, suggesting that condensates play a key role in tumorigenesis. In this review, we summarize and discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 205 publications
(268 reference statements)
1
75
0
Order By: Relevance
“…Emerging evidence begins to link cancer-related genes to condensate assembly, indicative of the important role of phase separation in tumorigenesis 26 . Boulay et al find that the phase separation of EWS–FLI1 fusion promotes the formation of super-enhancers and oncogenic transcriptional programs in Ewing sarcoma cancer 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence begins to link cancer-related genes to condensate assembly, indicative of the important role of phase separation in tumorigenesis 26 . Boulay et al find that the phase separation of EWS–FLI1 fusion promotes the formation of super-enhancers and oncogenic transcriptional programs in Ewing sarcoma cancer 27 .…”
Section: Discussionmentioning
confidence: 99%
“…These cellular processes have been the subject of much study, producing a deep mechanistic understanding of cellular regulation in both normal and transformed cells and providing therapeutic hypotheses that have yielded advances in medicine (Chmielecki and Meyerson, 2014;Sawyers, 2004;Vogelstein et al, 2013). Recent studies, however, have revealed that most cellular processes are compartmentalized in biomolecular condensates, which have physicochemical properties that contribute to regulatory mechanisms beyond those anticipated by conventional molecular biology (Banani et al, 2017;Choi et al, 2020;Forman-Kay et al, 2018;Hyman et al, 2014;Jiang et al, 2020;Shin and Brangwynne, 2017). This new understanding has compelled us and others to examine how condensate biology contributes to oncogenesis and consider new therapeutic hypotheses that might be exploited to benefit cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…The authors developed “deepDegron”, a machine learning method that predicts the impact of mutations or degron loss on protein stability, and validated these predictions for mutations in the degrons of GATA3 and PPM1D that result in stable proteins. Interestingly, in many cases, degrons are localized to intrinsically disordered regions (IDRs), and recent studies suggest that recognition, ubiquitination, and degradation take place in a unique physical environment involving phase separation [ 42 , 43 ].…”
Section: Evading Recognition I: Protein Stabilization Due To Lacking or Mutated Degradation Signalsmentioning
confidence: 99%